Single nucleotide polymorphism in coronary artery disease as in-stent restenosis risk factor (Journal of Medical Science, 2016)
In-stent restenosis (ISR) is a challenging complication of coronary stent implantation in both stable coronary artery disease (CAD) and acute coronary syndrome (ACS). Recent scientific aproach enables looking closely into its genetic background. This article briefly highlights the already known to increase susceptibility of ISR genetic polymorphisms and summarizes which were not proven to increase the risk of ISR and which may seem protective among CAD patients.